Tobacco Smoking Addiction: Epidemiology, Genetics, Mechanisms, and Treatment - Li, Ming D. (Springer Singapore, 2018)
This book provides the most recent knowledge on almost all key aspects of the health impact of tobacco smoking. Its 21 chapters focus on both preclinical and clinical studies. The contents are broad, covering the epidemiology of tobacco smoking; genetic epidemiology; identification of susceptibility genomic regions, genes, and pathways as determined by both human and animal studies; evolutionary relations among the different nAChR subunit genes that are so important to the nicotine response; smoking-related diseases; E-cigarettes; and smoking cessation. Furthermore, each chapter includes a detailed and comprehensive list of key references. For both clinical and basic researchers, this book is a valuable resource on nicotine dependence and other addictions.